PVA fiber toughened geopolymer and preparation method thereof
A PVA fiber-reinforced geopolymer preparation method addresses dispersibility and mechanical property issues by using specific ratios of PVA fiber and modified fibers, enhancing strength, toughness, and reducing cracking and shrinkage.
Patent Information
- Application Number
- CN202411099950.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-12
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The addition of PVA fiber, fly ash, and slag in geopolymers can lead to issues such as poor dispersibility, stress concentration, decreased mechanical properties, and decreased fluidity if the addition amounts and ratios are inappropriate, resulting in poor performance.
A method for preparing a PVA fiber-reinforced geopolymer by mixing fly ash, slag, and aggregates with an alkali activating solution, followed by adding a PVA fiber composition comprising specific ratios of PVA fiber, metakaolin-modified PVA fiber, and sodium lignin sulfonate-modified PVA fiber, with controlled amounts to improve dispersibility and mechanical properties.
The method enhances the dynamic compressive strength and toughness of the geopolymer, reduces cracking and shrinkage, and improves fluidity by optimizing the composition and ratios of PVA fiber and other components.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of geopolymers, and specifically discloses a PVA fiber-reinforced geopolymer and a preparation method thereof. Background Art
[0002] Geopolymer is a green gel material made from industrial solid waste such as fly ash and blast furnace slag. It is produced through a depolymerization-condensation reaction after alkali excitation. It has the characteristics of high early strength, good adhesion and durability, and is considered to be an ideal material to replace cement.
[0003] The addition of polyvinyl alcohol (PVA) fiber, fly ash, slag and other materials can improve crack resistance, enhance toughness, reduce shrinkage, etc.; however, their addition amount and ratio have an important influence on the performance of geopolymers. If the addition amount is inappropriate, it may lead to problems such as poor dispersibility, stress concentration, decreased mechanical properties, and decreased fluidity. Therefore, it is of great significance to study a PVA fiber-toughened geopolymer with a reasonable raw material ratio and its preparation method to obtain a geopolymer with good strength, good toughness, no cracking, and low shrinkage. Summary of the invention
[0004] The object of the present invention is to provide a PVA fiber toughened polymer and a preparation method thereof to solve the problems raised in the above background technology.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: A method for preparing a PVA fiber-reinforced geopolymer, characterized in that it comprises the following steps: mixing fly ash, slag, coarse aggregate and fine aggregate for 1 to 2 minutes, adding an alkali activating solution, stirring for 1 to 2 minutes, adding a PVA fiber composition, and mixing for 1 to 2 minutes to obtain a PVA fiber-reinforced geopolymer; The PVA fiber composition comprises PVA fiber, metakaolin-modified PVA fiber, and sodium lignin sulfonate-modified PVA fiber in a mass ratio of 4:(4-6):(1-2).
[0006] More optimally, the added amount of the PVA fiber composition is 2-3.5% of the mass of the PVA fiber toughening polymer.
[0007] More optimally, the fly ash content in the PVA fiber-reinforced geopolymer is 550-580 kg / m 3 The mass ratio of fly ash and slag is 1: (1~1.5); the amount of fine aggregate in PVA fiber toughened geopolymer is 650~710kg / m 3 The dosage of coarse aggregate in PVA fiber toughened geopolymer is 690~750kg / m 3 .
[0008] Optimally, the density of fly ash is 2.15 g / cm 3 , bulk density is 0.78g / cm 3 , standard consistency is 47.1%, water content is 0.62%; the components and contents of fly ash are: 60.98% SiO2, 24.47% Al2O3, 6.7% Fe2O3, 4.9% CaO, 0.68% MgO, 0.58% f-CaO, 0.52% SO3, and the rest are impurities; The fine aggregate is natural river sand with a fineness modulus of 3.0 produced by the Nanyang Sand Mining Field in Henan Province, and the coarse aggregate is natural crushed stone with a particle size of 10-20 mm produced by Nanjing Huiju Stone Co., Ltd. The slag was blast furnace slag produced by Gongyi Water Purification Materials Co., Ltd. (Henan, China).
[0009] More optimally, the PVA fiber, the metakaolin-modified PVA fiber, and the sodium lignin sulfonate-modified PVA fiber are respectively made of PVA powder, metakaolin-modified PVA, and sodium lignin sulfonate-modified PVA as raw materials, and are sequentially spun, wet-heat stretched, washed, dried, dry-heat stretched, heat-set, cross-linked, and cut after cooling; The lengths of the PVA fibers, metakaolin-modified PVA fibers, and sodium lignin sulfonate-modified PVA fibers are 14 to 16 mm.
[0010] More optimally, the preparation of the PVA fiber, the metakaolin-modified PVA fiber, and the sodium lignin sulfonate-modified PVA fiber respectively comprises the following steps: taking 20 to 25 parts of raw materials and adding them to 100 parts of water to obtain a spinning solution, and spinning; the coagulation bath comprises 70 to 80 g / L of sulfuric acid, 6 to 10.0 g / L of zinc sulfate, 350 to 380 g / L of sodium sulfate, and the rest is water; the drop of the coagulation bath concentration is 6.0 to 10.0 g / L, the coagulation bath temperature is 42 to 45°C, the spinneret draft is 10%, the residence time of the filaments in the coagulation bath is 10 to 15 s, and the spinning speed is 42 to 45 m / s; wet heat stretching is performed: the wet heat stretching bath comprises 360 to 400 g / L of sodium sulfate; 00g / L, sulfuric acid 5.0~10.0g / L, and the rest is water; temperature 90~94℃, the treatment time of the filament bundle in the bath is 2.0~3.0s, and the wet heat drawing multiple is 30~50%; water washing at 40~42℃; drying at 120~130℃; dry heat stretching: temperature 200~210℃, time 80~90s, stretching multiple 60~80%; heat setting: temperature 230~240℃, time 50~60s, rapid cooling to 40~45℃; crosslinking: crosslinking in 40~50g / L glyoxal aqueous solution for 10~15min, cutting after cooling, and obtaining PVA fiber / metakaolin modified PVA fiber / sodium lignin sulfonate modified PVA fiber respectively.
[0011] Among them, the raw material of PVA fiber is PVA powder; the raw material of metakaolin-modified PVA fiber is metakaolin-modified PVA and PVA powder in a mass ratio of 3:2; the raw material of sodium lignin sulfonate-modified PVA fiber is sodium lignin sulfonate-modified PVA and PVA powder in a mass ratio of 4:1; More optimally, the preparation of the PVA fiber, the kaolin-modified PVA fiber, and the sodium lignin sulfonate-modified PVA fiber respectively includes the following steps: taking 20 parts of raw materials and adding them to 100 parts of water to obtain a spinning solution, and spinning; the coagulation bath is composed of 80g / L sulfuric acid, 10.0g / L zinc sulfate, 380g / L sodium sulfate, and the rest is water; the drop of the coagulation bath concentration is 10.0g / L, the coagulation bath temperature is 42°C, the spinneret is drawn by 10%, the residence time of the filament in the coagulation bath is 10s, and the spinning speed is 45m / s; wet heat stretching: wet heat stretching The stretching bath liquid is composed of 360g / L sodium sulfate, 10.0g / L sulfuric acid, and the rest is water; the temperature is 90°C, the treatment time of the filament bundle in the bath liquid is 2.0s, and the wet heat stretching multiple is 30%; water washing at 40°C; drying at 120°C; dry heat stretching: temperature 200°C, time 90s, stretching multiple 80%; heat setting: temperature 230°C, time 50s, rapid cooling to 40°C; cross-linking: cross-linking in 40g / L glyoxal aqueous solution for 15min, cutting after cooling, and obtaining PVA fiber / metakaolin modified PVA fiber / sodium lignin sulfonate modified PVA fiber respectively.
[0012] More optimally, the preparation of the metakaolin-modified PVA comprises the following steps: S1: adding PVA powder to water, stirring to dissolve, cooling to room temperature, adjusting the pH to 3-3.5, adding glutaraldehyde solution, stirring at 60-70° C. for 10-12 hours, removing the solvent, washing, and drying to obtain glutaraldehyde-modified PVA; S2: Put the metakaolin into a dispersing machine, add triethanolamine, and disperse for 30-35 minutes to obtain triethanolamine-modified metakaolin; take the triethanolamine-modified metakaolin, add it into water and disperse it evenly, add glutaraldehyde and 4-methyl-2-pentanol, stir at 50-60° C. for 2-3 hours, filter and dry, and obtain 4-methyl-2-pentanol-modified metakaolin; S3: Take glutaraldehyde-modified PVA, add it into water and stir evenly, add 4-methyl-2-pentanol-modified kaolin, react at 50-60°C for 10-12h, remove the solvent, wash and dry to obtain kaolin-modified PVA.
[0013] More optimally, the glutaraldehyde-modified PVA comprises the following raw materials, calculated by weight: 10-15 parts of PVA powder, 100 parts of water, and 50-60 parts of 2 mol / L glutaraldehyde solution; in the triethanolamine-modified metakaolin, the weight of metakaolin and triethanolamine is (100-120): 1; The 4-methyl-2-pentanol modified metakaolin comprises the following raw materials, calculated by weight: 100 parts of triethanolamine modified metakaolin, 3-5 parts of glutaraldehyde, and 4-5 parts of 4-methyl-2-pentanol; the amount of water added is 8-10 times the weight of the triethanolamine modified metakaolin; The metakaolin-modified PVA comprises the following raw materials, calculated by weight: 10 to 15 parts of glutaraldehyde-modified PVA, 100 parts of water, and 5 to 8 parts of 4-methyl-2-pentanol-modified metakaolin.
[0014] More optimally, the preparation of the sodium lignin sulfonate modified PVA includes the following steps: taking glutaraldehyde modified PVA, adding it into water and stirring evenly, adding nano-silicon dioxide and sodium lignin sulfonate, reacting at 50-60° C. for 4-6 hours, removing the solvent, washing, and drying to obtain the sodium lignin sulfonate modified PVA.
[0015] More optimally, the sodium lignin sulfonate modified PVA includes the following raw materials, calculated by weight: 10-15 parts of glutaraldehyde modified PVA, 100 parts of water, 3-5 parts of nano-silicon dioxide, and 3-5 parts of sodium lignin sulfonate.
[0016] More optimally, the nano-silicon dioxide is ML-SiO2-N22 produced by Zhejiang Manli Nanotechnology Co., Ltd., with a particle size of 20 nm and treated with KH550.
[0017] More optimally, the preparation of the alkaline activating solution includes the following steps: mixing sodium hydroxide and water to obtain a sodium hydroxide solution, cooling to room temperature for 24 hours, and then adding water glass to the sodium hydroxide solution and stirring evenly to obtain an alkaline activating solution; the mass ratio of sodium hydroxide to water glass is 1: (9-10), and the amount of water added is 0.5-0.7 times the mass of water glass; the amount of water glass added to the PVA fiber toughening polymer is 180kg / m 3 .
[0018] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: (1) the dynamic compressive strength and toughness of the geopolymer are improved and cracking and shrinkage are reduced by controlling the added ratio of fly ash / slag and the added amount of the PVA fiber composition; the PVA fiber composition comprises a certain mass ratio of PVA fiber, kaolin-modified PVA fiber, and sodium lignin sulfonate-modified PVA fiber; the PVA fiber has a light weight and good alkali resistance, can be randomly distributed in the geopolymer, can bridge the internal cracks of the geopolymer, and bear part of the internal stress and reduce the shrinkage rate; the addition of kaolin to the kaolin-modified PVA fiber helps to improve the mechanical properties. The present invention first allows triethanolamine to be adsorbed on the surface of the kaolin through physical and chemical actions under mechanical action, and then enters the surface of the kaolin. The interspaces between the metakaolin particles are agglomerated, the dispersibility of the metakaolin is improved, and the surface of the metakaolin has groups that can participate in the next reaction, and then 4-methyl-2-pentanol is added for modification, which improves the problem of decreased fluidity caused by the addition of the metakaolin. Due to the improved fluidity, the dispersibility is also better, and the mechanical properties are improved accordingly; the sodium lignin sulfonate-modified PVA includes nano-silicon dioxide and sodium lignin sulfonate, which makes up for the defect of low compressive strength of the PVA fiber, and the sodium lignin sulfonate has the effect of a water reducer, reduces the amount of water added and further improves the fluidity; after adding the PVA fiber composition prepared by the present invention, the dynamic compression strength and toughness of the geopolymer are significantly improved, and the cracking rate and shrinkage rate are reduced; but the addition amount should not be too large, otherwise it will lead to poor dispersibility and reduced performance. DETAILED DESCRIPTION
[0019] The following is a preferred implementation of the embodiment of the present invention. Obviously, the described embodiment is only a part of the embodiment of the present invention, not all of the embodiments. For ordinary technicians in this technical field, all other embodiments obtained by ordinary technicians in this field without creative work without departing from the principle of the embodiment of the present invention are within the scope of protection of the present invention.
[0020] The following parts are by mass unless otherwise specified; Example 1: S1: Sodium hydroxide and water are mixed to obtain a sodium hydroxide solution, which is cooled to room temperature for 24 hours, and then water glass is added to the sodium hydroxide solution and stirred evenly to obtain an alkali excitation solution; the mass ratio of the sodium hydroxide to the water glass is 1:10, and the amount of water added is 0.6 times the mass of the water glass; S2: Put kaolin and triethanolamine in a mass ratio of 100:1 into a dispersing machine and dispers them for 35 minutes to obtain triethanolamine-modified kaolin; take 100 parts of triethanolamine-modified kaolin, add water 10 times its mass, disperse evenly, add 4 parts of glutaraldehyde and 5 parts of 4-methyl-2-pentanol, stir at 60°C for 3 hours, filter and dry, and obtain 4-methyl-2-pentanol-modified kaolin; S3: Take 12 parts of PVA powder and add it to 100 parts of water, heat it to 90°C and stir to dissolve, cool it to room temperature, add dilute hydrochloric acid to adjust the pH to 3, add 55 parts of 2 mol / L glutaraldehyde solution, stir at 70°C for 12 hours, remove the solvent, wash and dry to obtain glutaraldehyde-modified PVA; S4: Take 12 parts of glutaraldehyde-modified PVA, add it to 100 parts of water and stir evenly, add 6 parts of 4-methyl-2-pentanol-modified metakaolin, react at 60° C. for 12 hours, remove the solvent, wash, and dry to obtain metakaolin-modified PVA; S5: Take 12 parts of glutaraldehyde-modified PVA, add it to 100 parts of water and stir evenly, add 5 parts of nano-silicon dioxide and 4 parts of sodium lignin sulfonate, react at 60°C for 5 hours, remove the solvent, wash and dry to obtain sodium lignin sulfonate-modified PVA; S6: PVA powder, metakaolin-modified PVA, and sodium lignin sulfonate-modified PVA are respectively made into 15 mm PVA fibers, metakaolin-modified PVA fibers, and sodium lignin sulfonate-modified PVA fibers, and the mixture is uniformly mixed in a mass ratio of 4:6:1 to obtain a PVA fiber composition; S7: fly ash, slag, coarse aggregate and fine aggregate were mixed for 2 minutes, alkali activating solution was added, stirred for 2 minutes, and PVA fiber composition with a weight percentage of 3% of PVA fiber toughened geopolymer was added, mixed for 2 minutes to obtain PVA fiber toughened geopolymer; the fly ash dosage was 577kg / m 3 The mass ratio of fly ash and slag is 1:1.5; the amount of fine aggregate is 690kg / m 3 The dosage of coarse aggregate is 695kg / m 3 The dosage of water glass is 180kg / m 3 .
[0021] Example 2: S1: Sodium hydroxide and water are mixed to obtain a sodium hydroxide solution, which is cooled to room temperature for 24 hours, and then water glass is added to the sodium hydroxide solution and stirred evenly to obtain an alkali excitation solution; the mass ratio of the sodium hydroxide to the water glass is 1:10, and the amount of water added is 0.7 times the mass of the water glass; S2: Put kaolin and triethanolamine in a mass ratio of 100:1 into a dispersing machine and dispers them for 35 minutes to obtain triethanolamine-modified kaolin; take 100 parts of triethanolamine-modified kaolin, add water 10 times its mass, disperse evenly, add 5 parts of glutaraldehyde and 5 parts of 4-methyl-2-pentanol, stir at 60°C for 3 hours, filter and dry, and obtain 4-methyl-2-pentanol-modified kaolin; S3: Take 15 parts of PVA powder and add it to 100 parts of water, heat it to 90°C and stir to dissolve, cool it to room temperature, add dilute hydrochloric acid to adjust the pH to 3, add 60 parts of 2 mol / L glutaraldehyde solution, stir at 70°C for 12 hours, remove the solvent, wash and dry to obtain glutaraldehyde-modified PVA; S4: Take 15 parts of glutaraldehyde-modified PVA, add it to 100 parts of water and stir evenly, add 8 parts of 4-methyl-2-pentanol-modified metakaolin, react at 60° C. for 12 hours, remove the solvent, wash, and dry to obtain metakaolin-modified PVA; S5: Take 15 parts of glutaraldehyde-modified PVA, add it to 100 parts of water and stir evenly, add 5 parts of nano-silicon dioxide and 5 parts of sodium lignin sulfonate, react at 60°C for 5 hours, remove the solvent, wash and dry to obtain sodium lignin sulfonate-modified PVA; S6: PVA powder, metakaolin-modified PVA, and sodium lignin sulfonate-modified PVA are respectively made into 15 mm PVA fibers, metakaolin-modified PVA fibers, and sodium lignin sulfonate-modified PVA fibers, and the mixture is uniformly mixed in a mass ratio of 4:5:1 to obtain a PVA fiber composition; S7: fly ash, slag, coarse aggregate and fine aggregate were mixed for 2 minutes, alkali activating solution was added, stirred for 2 minutes, and PVA fiber composition with a weight percentage of 3% of PVA fiber toughened geopolymer was added, mixed for 2 minutes to obtain PVA fiber toughened geopolymer; the fly ash dosage was 577kg / m 3 The mass ratio of fly ash and slag is 1:1.5; the amount of fine aggregate is 690kg / m 3 The dosage of coarse aggregate is 695kg / m 3 The dosage of water glass is 180kg / m 3 .
[0022] Example 3: S1: Sodium hydroxide and water are mixed to obtain a sodium hydroxide solution, which is cooled to room temperature for 24 hours, and then water glass is added to the sodium hydroxide solution and stirred evenly to obtain an alkali excitation solution; the mass ratio of the sodium hydroxide to the water glass is 1:10, and the amount of water added is 0.5 times the mass of the water glass; S2: Put kaolin and triethanolamine in a mass ratio of 100:1 into a dispersing machine and dispers them for 35 minutes to obtain triethanolamine-modified kaolin; take 100 parts of triethanolamine-modified kaolin, add water 10 times its mass, disperse evenly, add 3 parts of glutaraldehyde and 4 parts of 4-methyl-2-pentanol, stir at 60°C for 3 hours, filter and dry, and obtain 4-methyl-2-pentanol-modified kaolin; S3: Take 10 parts of PVA powder and add it to 100 parts of water, heat it to 90°C and stir to dissolve, cool it to room temperature, add dilute hydrochloric acid to adjust the pH to 3, add 50-60 parts of 2 mol / L glutaraldehyde solution, stir at 70°C for 12 hours, remove the solvent, wash and dry to obtain glutaraldehyde-modified PVA; S4: Take 10 parts of glutaraldehyde-modified PVA, add it to 100 parts of water and stir evenly, add 5 parts of 4-methyl-2-pentanol-modified metakaolin, react at 60° C. for 12 hours, remove the solvent, wash, and dry to obtain metakaolin-modified PVA; S5: Take 10 parts of glutaraldehyde-modified PVA, add it to 100 parts of water and stir evenly, add 3 parts of nano-silicon dioxide and 5 parts of sodium lignin sulfonate, react at 60°C for 5 hours, remove the solvent, wash and dry to obtain sodium lignin sulfonate-modified PVA; S6: PVA powder, metakaolin-modified PVA, and sodium lignin sulfonate-modified PVA are respectively made into 15 mm PVA fibers, metakaolin-modified PVA fibers, and sodium lignin sulfonate-modified PVA fibers, and the mixture is uniformly mixed in a mass ratio of 4:6:2 to obtain a PVA fiber composition; S7: fly ash, slag, coarse aggregate and fine aggregate were mixed for 2 minutes, alkali activating solution was added, stirred for 2 minutes, and PVA fiber composition with a weight percentage of 3% of PVA fiber toughened geopolymer was added, mixed for 2 minutes to obtain PVA fiber toughened geopolymer; the fly ash dosage was 577kg / m 3 The mass ratio of fly ash and slag is 1:1.5; the amount of fine aggregate is 690kg / m 3 The dosage of coarse aggregate is 695kg / m 3 The dosage of water glass is 180kg / m 3 .
[0023] Comparative Example 1 (the mass ratio of PVA fiber, metakaolin-modified PVA fiber, and sodium lignin sulfonate-modified PVA fiber was changed, and the other method steps were consistent with Example 1): S1: PVA powder, metakaolin-modified PVA, and sodium lignin sulfonate-modified PVA were respectively made into 15 mm PVA fiber, metakaolin-modified PVA fiber, and sodium lignin sulfonate-modified PVA fiber, and the mixture was uniformly mixed at a mass ratio of 8:2:1 to obtain a PVA fiber composition; S2: fly ash, slag, coarse aggregate and fine aggregate were mixed for 2 minutes, alkali activating solution was added, stirred for 2 minutes, 3% of the mass of PVA fiber toughened geopolymer by PVA fiber composition was added, and mixed for 2 minutes to obtain PVA fiber toughened geopolymer.
[0024] Comparative Example 2 (increasing the amount of 4-methyl-2-pentanol added to the kaolin-modified PVA, and the remaining method steps are consistent with Example 1): S1: Put kaolin and triethanolamine in a mass ratio of 100:1 into a disperser, and disperse for 35 minutes to obtain triethanolamine-modified kaolin; take 100 parts of triethanolamine-modified kaolin, add 10 times its mass of water, disperse evenly, add 4 parts of glutaraldehyde and 10 parts of 4-methyl-2-pentanol, stir at 60° C. for 3 hours, filter and dry, and obtain 4-methyl-2-pentanol-modified kaolin; S2: fly ash, slag, coarse aggregate and fine aggregate were mixed for 2 minutes, alkali activating solution was added, stirred for 2 minutes, 3% of the mass of PVA fiber toughened geopolymer by PVA fiber composition was added, and mixed for 2 minutes to obtain PVA fiber toughened geopolymer.
[0025] Comparative Example 3 (the preparation method of the PVA fiber composition is changed, and the remaining steps are consistent with Example 1): S1: Take 12 parts of glutaraldehyde-modified PVA, add it to 100 parts of water and stir evenly, add 6 parts of 4-methyl-2-pentanol-modified metakaolin, 5 parts of nano-silica, and 4 parts of sodium lignin sulfonate, react at 60° C. for 12 hours, remove the solvent, wash, and dry to obtain modified PVA; S2: PVA powder and modified PVA are respectively made into 15 mm PVA fibers and modified PVA fibers, and the mixture is uniformly mixed in a mass ratio of 4:7 to obtain a PVA fiber composition; S3: fly ash, slag, coarse aggregate and fine aggregate are mixed for 2 minutes, alkali activating solution is added, stirred for 2 minutes, and a PVA fiber composition of 3% by weight of the PVA fiber toughened geopolymer is added, mixed for 2 minutes to obtain a PVA fiber toughened geopolymer.
[0026] Comparative Example 4 (increasing the amount of PVA fiber composition added, the remaining steps are consistent with Example 1): S1: fly ash, slag, coarse aggregate and fine aggregate are mixed for 2 minutes, alkali activating solution is added, stirred for 2 minutes, and PVA fiber composition with a weight of 4.5% of PVA fiber toughened geopolymer is added, mixed for 2 minutes to obtain PVA fiber toughened geopolymer; the amount of fly ash is 577kg / m 3 The mass ratio of fly ash and slag is 1:1.5; the amount of fine aggregate is 690kg / m 3 The dosage of coarse aggregate is 695kg / m 3 The dosage of water glass is 180kg / m 3 .
[0027] In the above embodiments, the test methods used are conventional methods unless otherwise specified; the raw materials used are commercially available unless otherwise specified, and the sources of the raw materials are as follows: ethanol (CAS: 64-17-5); glutaraldehyde (CAS: 111-30-8); water glass (CAS: 1344-09-8); sodium hydroxide (CAS: 1310-73-2); metakaolin (A00379, Wuhan Jiyesheng Chemical Co., Ltd.); triethanolamine (CAS: 102-71-6); glutaraldehyde (CAS: 111-30-8); 4-methyl-2-pentanol (CAS: 108-11-2); PVA powder (polyvinyl alcohol 1788, Hubei Kangdisi Chemical Co., Ltd.); sodium lignin sulfonate (S30635, Shanghai Yuanye); zinc sulfate (S22124, Shanghai Yuanye); sodium sulfate (S24155, Shanghai Yuanye); glyoxal (CAS: 107-22-2).
[0028] Experiment 1: Take the PVA fiber toughened geopolymers prepared in Examples 1 to 3 and Comparative Examples 1 to 4, and test their dynamic compression strength and toughness according to the standard GB-T50081-2019; the specific data are shown in Table 1; Table 1:
[0029] Experiment 2: (1) With reference to JC / T951-2005, the crack resistance was tested in a walk-in constant temperature and humidity test system; the ambient temperature was 20°C, the relative humidity was 60%, and the test was carried out after 4 hours of light exposure and 24 hours of wind blowing at a wind speed of about 3.0 m / s; (2) With reference to JGJ / T70-2009, the drying shrinkage test was carried out, and the samples were cured for 1 day in a standard curing box at 20°C and a relative humidity of >95%, and then placed in a constant temperature and humidity drying box at 20°C and a relative humidity of 60% for 4 hours, and the shrinkage rate at 28 days was measured using a vertical shrinkage tester; specific data are shown in Table 2; Table 2:
[0030] Conclusion: (1) Compared with the geopolymer without adding PVA fiber composition, Example 1 with the best performance has a dynamic compression strength increased by 2.3 times and a toughness increased by 3.0 times; (2) In Comparative Example 1, the mass ratio of PVA fiber, kaolin-modified PVA fiber, and sodium lignin sulfonate-modified PVA fiber was changed, resulting in a decrease in performance. It can be seen that the ratio of PVA fiber composition is of great significance; Comparative Example 2 increases the amount of 4-methyl-2-pentanol added in kaolin-modified PVA, and the performance is not as good as in Example 1; Comparative Example 3 changes the mass ratio of PVA fiber to that of kaolin-modified PVA. The preparation method of the composition comprises the following steps: using glutaraldehyde-modified PVA, 4-methyl-2-pentanol-modified metakaolin, nano-silica and sodium lignin sulfonate to prepare modified PVA, which replaces metakaolin-modified PVA and sodium lignin sulfonate-modified PVA. The performance of the modified PVA is reduced due to problems of grafting rate and dispersibility. In comparative example 4, the added amount of the PVA fiber composition is increased, and the performance is reduced, so it can be seen that the added amount needs to be controlled. In summary, the PVA fiber-reinforced geopolymer prepared by the present invention has good dynamic compression strength and toughness, is not easy to crack, and has a low shrinkage rate.
[0031] Finally, it should be noted that the above is only a preferred embodiment of the present invention, but the protection scope of this application is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the technical field within the spirit and principle of the present invention and within the technical scope disclosed in this application should be included in the protection scope of this application; in the absence of conflict, the embodiments of this application and the features in the embodiments can be combined with each other. Therefore, the protection scope of this application shall be based on the protection scope of the claims.
Claims
1. A method for preparing a PVA fiber-reinforced geopolymer, characterized in that: The following steps are involved: The fly ash, slag, coarse aggregate and fine aggregate are mixed for 1-2 minutes, an alkali activating solution is added, the mixture is stirred for 1-2 minutes, a PVA fiber composition is added, and the mixture is mixed for 1-2 minutes to obtain a PVA fiber toughened geopolymer; The PVA fiber composition comprises PVA fiber, metakaolin-modified PVA fiber, and sodium lignin sulfonate-modified PVA fiber in a mass ratio of 4:(4-6):(1-2).
2. The method for preparing a PVA fiber-reinforced geopolymer according to claim 1, characterized in that: The added amount of the PVA fiber composition is 2-3.5% of the mass of the PVA fiber toughening polymer.
3. The method for preparing a PVA fiber-reinforced geopolymer according to claim 1, characterized in that: The fly ash content in the PVA fiber-reinforced geopolymer is 550-580 kg / m 3 The mass ratio of fly ash and slag is 1: (1~1.5); the amount of fine aggregate in PVA fiber toughened geopolymer is 650~710kg / m 3 The dosage of coarse aggregate in PVA fiber toughened geopolymer is 690~750kg / m 3 .
4. The method for preparing a PVA fiber-reinforced geopolymer according to claim 1, characterized in that: The PVA fiber, metakaolin-modified PVA fiber, and sodium lignin sulfonate-modified PVA fiber are respectively made from PVA powder, metakaolin-modified PVA, and sodium lignin sulfonate-modified PVA as raw materials, and are sequentially spun, wet-heat stretched, washed, dried, dry-heat stretched, heat-set, cross-linked, and cut after cooling; The lengths of the PVA fibers, metakaolin-modified PVA fibers, and sodium lignin sulfonate-modified PVA fibers are 14 to 16 mm.
5. The method for preparing a PVA fiber-reinforced geopolymer according to claim 4, characterized in that: The preparation of the metakaolin-modified PVA comprises the following steps: S1: PVA powder is added into water, stirred to dissolve, cooled to room temperature, pH adjusted to 3-3.5, glutaraldehyde solution is added, stirred at 60-70°C for 10-12h, the solvent is removed, washed, and dried to obtain glutaraldehyde-modified PVA; S2: Put the metakaolin into a dispersing machine, add triethanolamine, and disperse for 30-35 minutes to obtain triethanolamine-modified metakaolin; take the triethanolamine-modified metakaolin, add it into water and disperse it evenly, add glutaraldehyde and 4-methyl-2-pentanol, stir at 50-60° C. for 2-3 hours, filter and dry, and obtain 4-methyl-2-pentanol-modified metakaolin; S3: Take glutaraldehyde-modified PVA, add it into water and stir evenly, add 4-methyl-2-pentanol-modified kaolin, react at 50-60°C for 10-12h, remove the solvent, wash and dry to obtain kaolin-modified PVA.
6. The method for preparing a PVA fiber-reinforced geopolymer according to claim 5, characterized in that: The glutaraldehyde-modified PVA comprises the following raw materials, calculated by weight: 10-15 parts of PVA powder, 100 parts of water, and 50-60 parts of 2 mol / L glutaraldehyde solution; In the triethanolamine-modified metakaolin, the mass ratio of metakaolin to triethanolamine is (100-120):1; The 4-methyl-2-pentanol modified metakaolin comprises the following raw materials, calculated by weight: 100 parts of triethanolamine modified metakaolin, 3-5 parts of glutaraldehyde, and 4-5 parts of 4-methyl-2-pentanol; The metakaolin-modified PVA comprises the following raw materials, calculated by weight: 10 to 15 parts of glutaraldehyde-modified PVA, 100 parts of water, and 5 to 8 parts of 4-methyl-2-pentanol-modified metakaolin.
7. The method for preparing a PVA fiber-reinforced geopolymer according to claim 4, characterized in that: The preparation of the sodium lignin sulfonate modified PVA comprises the following steps: Take glutaraldehyde-modified PVA, add it into water and stir evenly, add nano-silica and sodium lignin sulfonate, react at 50-60°C for 4-6 hours, remove the solvent, wash and dry to obtain sodium lignin sulfonate-modified PVA.
8. The method for preparing a PVA fiber-reinforced geopolymer according to claim 7, characterized in that: The sodium lignin sulfonate modified PVA comprises the following raw materials, calculated by weight: 10-15 parts of glutaraldehyde modified PVA, 100 parts of water, 3-5 parts of nano silicon dioxide, and 3-5 parts of sodium lignin sulfonate.
9. The method for preparing a PVA fiber-reinforced geopolymer according to claim 1, characterized in that: The preparation of the alkali activating solution comprises the following steps: mixing sodium hydroxide and water to obtain a sodium hydroxide solution, cooling for 24 hours to room temperature, and then adding water glass to the sodium hydroxide solution and stirring evenly to obtain the alkali activating solution; the mass ratio of sodium hydroxide to water glass is 1: (9-10), and the amount of water added is 0.5-0.7 times the mass of water glass; the amount of water glass added to the PVA fiber toughening polymer is 180kg / m 3 .
10. A PVA fiber-reinforced geopolymer prepared according to the method for preparing a PVA fiber-reinforced geopolymer according to any one of claims 1 to 9.
Citation Information
Cited By
PVA fiber reinforced geopolymer material and preparation method thereof
CN121085581A
A pva fiber-reinforced geopolymer material and a method for producing the same
CN121085581B
Compression-resistant geopolymer material containing PVA (Polyvinyl Alcohol) fiber and preparation method of compression-resistant geopolymer material
CN121824028A
A compression-resistant geopolymer material containing pva fibers and a method of making the same
CN121824028B